Mitigating the repercussions of climate change on diseases affecting important crop commodities in Southeast Asia, for food security and environmental sustainability—A review - Lim, Jie Ann; Yaacob, Jamilah Syafawati; Mohd Rasli, Siti Rasila Ainaa; Eyahmalay, Jennifer Edwina; El Enshasy, Hesham Ali; Zakaria, Mohd Rezuwan Shah (Frontiers in Sustainable Food Systems, 2023)
Southeast Asia is a fertile land with a warm and humid climate which tends to accommodate various food crops. The development and advancement of the agricultural sector not only allows the countries in the region to feed the increasing population, but are also able to boost the nation’s economy through exportation of the crops. Some of the well-known and economically-significant plant commodities found in the region include rice, oil palm, rubber, coconut, banana, sugarcane, pineapple, black pepper, maize, cocoa, durian and jackfruit. Due to the high production of crops, Southeast Asia is able to stand among the top world producers of these commodities. Nevertheless, the widespread of pathogenic microorganisms has posed a serious threat to the industry over the years; with hundreds of millions of money wasted and total yield being lost due to the devastating diseases associated with each type of the plants. A lot of attention and effort have been continuously devoted to find effective plant management strategies to combat plant diseases, starting from traditional physical and chemical methods towards the increasing discoveries on biological approaches made in recent decades. Due to the challenges and limitations faced by conventional approaches and the rising awareness towards the environment, more work has been focused on establishing the application of beneficial microorganisms to tackle plant diseases through direct mechanisms. Thus, by bringing the common plant commodities in Southeast Asia, their associated diseases and various physical, chemical and biological control measures together, this review aims to provide clearer insights and practical information to those who seek to limit the damages caused by plant diseases.